Exploring students' perspectives on communication apprehension in public speaking context: a focus on UTM mechanical engineering students - Che Abas, Atirah Izzah; Noordin, Nooreen; Abdullah, Arifuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
This study aims to explore the students’ perspectives on the factors of communication apprehension (CA), ways to alleviate it and their learning preferences in their English language classroom. Five Mechanical Engineering students from Universiti Teknologi Malaysia (UTM) were selected and interviewed individually. The results indicate that most of the respondents generally attributed the fear of assessment and big number of audiences to their CA and in order to overcome it, it was crucial for them to prepare well for the presentation particularly with regard to the content of their speech. Also, to alleviate their CA, the students preferred friendly and interactive lecturers as well as informal and comfortable environment in classroom. Besides, the students also showed interest in fun and interesting activities (ice breaking activities, group work and games) that were incorporated in the communication tasks. In all, the students’ perspectives on the issue of CA in English language classroom will further assist language instructors to understand the causes of CA, how the students’ cope with CA and how they wish the language classroom to be conducted to overcome the CA that they experience.